THE CORRELATIONS OF THE INTERNET ADDICTION BETWEEN COPING AND DEVIANT BEHAVIOUR OF STUDENTS - I. I. Hasanova; S. S. Kotova (Obrazovanie i Nauka)
Introduction. The Internet has become the powerful environmental factor of formation of the personality of modern young people exerting far ambiguous impact on them. Obviously, blurring of temporary and spatial distinctions between people thanks to the Internet resources look positive and very convenient for expeditious personal, social and business communications, essential simplification of search of necessary information, a possibility of distance learning, receiving the services «without leaving the house», etc. At the same time, the problem of the Internet and addictive behaviour among teenagers and young people, who are most vulnerable for any negative impacts by the reason of age immaturity, is becoming more and more urgent.The aim of the present publication is to study the problem of the correlations of the Internet addiction with coping and deviant behaviour of students, as well as the design the process of psycho-pedagogical correction of the Internet-addictive behaviour of students.Methodology and research methods. The leading research method is psychological-pedagogical observation. Questionnaire survey and psychological testing enabled to identify the interdependence between the Internet addiction, constructive ways of coping (confrontation, escape-avoidance) and deviant behaviour of students.Results and scientific novelty. The concept «Internet-addictive behavior» is redefined. Methodological approaches to the study of the Internet addiction interrelated with coping and deviant behaviour are presented and summarized. Individual-psychological characteristics of the Internet-addictive young people are studied out; a psychological portrait of the personality of the Internet-addictive students with given characteristics, personality traits, accentuations of character, social and emotional intelligence is worked out. The aims, tasks, principles and methods of correction of individual students with tendency to the Internet addiction are designated.Practical significance. The provided materials of the article are of practical value for psychologists, teachers-psychologists of the education system, working on the problem of psychological and pedagogical support of students and the implementation of development programs, and correctional-developing.